2021
DOI: 10.3389/fonc.2020.604266
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Pathological Upgrading at Radical Prostatectomy in Prostate Cancer Eligible for Active Surveillance: A Texture Features and Machine Learning-Based Analysis of Apparent Diffusion Coefficient Maps

Abstract: ObjectiveTo evaluate a combination of texture features and machine learning-based analysis of apparent diffusion coefficient (ADC) maps for the prediction of Grade Group (GG) upgrading in Gleason score (GS) ≤6 prostate cancer (PCa) (GG1) and GS 3 + 4 PCa (GG2).Materials and methodsFifty-nine patients who were biopsy-proven to have GG1 or GG2 and underwent MRI examination with the same MRI scanner prior to transrectal ultrasound (TRUS)-guided systemic biopsy were included. All these patients received radical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Various ML algorithms previously used for GG upgrade prediction are logistic regression 18 , LASSO regression 18 , 46 , SVM 18 , 47 , k-Nearest Neighbours (kNN) 46 , decision trees 46 , and random forests 18 , 46 . Due to the lack of large datasets, medical problems pose a particular challenge for ML models.…”
Section: Discussionmentioning
confidence: 99%
“…Various ML algorithms previously used for GG upgrade prediction are logistic regression 18 , LASSO regression 18 , 46 , SVM 18 , 47 , k-Nearest Neighbours (kNN) 46 , decision trees 46 , and random forests 18 , 46 . Due to the lack of large datasets, medical problems pose a particular challenge for ML models.…”
Section: Discussionmentioning
confidence: 99%
“…However, they noticed incremental benefit with the addition of clinical parameters. Another study by Xie et al investigated the role of radiomics from ADC maps to predict upgrading in Gleason score from TRUS-guided biopsies to radical prostatectomy (34). While Xie et al's study (34) did not directly address progression on repeat biopsy, they demonstrated that radiomic features from screening MRI can differentiate clinically significant and insignificant PCa.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, studies of Nordström et al and Moore et al demonstrated that the inclusion of MRI in longitudinal PCa biopsy and diagnostic pathways lead to a clear decrease of unnecessary re-biopsies and a higher yield of the clinical significant PCa ( 24 , 25 ). Those pathways are likely to further improve if combined with deep learning-based analyses of imaging features, such as apparent diffusion coefficient (ADC) maps ( 26 ).…”
Section: Discussionmentioning
confidence: 99%